Law and Literature - Sáenz, María Jimena (EUNOMÍA. Revista en Cultura de la Legalidad, 2019)
The relationship between law and literature is the object of study of the “law and literature movement”, an interdisciplinary enterprise that emerged in the 70s in the context of Anglophone academy. This paper offers a review of its origins, key authors, contexts and institutions, and presents a periodization of the work done in more than three decades, its migrations to the field of literary studies and the expansion across different legal cultures.